The ferroelectric phase transition in a 500 nm sized single particle of BaTiO3 tracked by coherent X-ray diffraction. (1st November 2022) - Oshime, Norihiro; Ohwada, Kenji; Machida, Akihiko; Fukushima, Nagise; Ueno, Shintaro; Fujii, Ichiro; Wada, Satoshi; Sugawara, Kento; Shimada, Ayumu; Ueno, Tetsuro; Watanuki, Tetsu; Ishii, Kenji; et al.
Abstract: The shapes and sizes of grains influence the anisotropy of crystal structures and the configuration of ferroelectric domains. In order to better understand these effects, we introduce a method to observe a ferroelectric phase transition in a single ferroelectric particle of sub-micrometer size. The phase transition was observed by cooling the sample through its Curie temperature, and studying the pattern variations of Bragg coherent X-ray diffraction from a single particle of 500 nm sized BaTiO3 . A change from a single 200 peak (cubic phase) to both 200 and 002 peaks (tetragonal phase); was seen, with fringes connecting them like a bridge. The pattern from the BaTiO3 particle in the cubic phase was also imaged using Bragg coherent diffraction imaging. The apparent strain distribution caused by dislocation internal to the BaTiO3 crystal was visible in the reconstructed image.